Xanthogranulomatous osteomyelitis - Monika Rathi; Jyotsana Khattri; Satish Kumar Budania; Jaskirat Singh; Seema Awasthi; Sushmit Verma (Archives of Medicine and Health Sciences, 2014)
Xanthogranulomatous inflammation in bone is a very rare entity. We came across this rare case of xanthogranulomatous osteomyelitis. We present a rare case of 50-year-old male who presented to the hospital with the chief complaint of pain and swelling in left ankle for 5 months and fever for 2 days. Total leukocyte count and differential leucocyte count was normal. Renal function tests and liver function tests were normal. Montoux test was negative. Chest X-ray was normal. Pus culture was negative for acid-fast bacilli but showed heavy growth of Pseudomonas. X-ray imaging revealed soft tissue mass, periosteal reaction and cortical disruption in the lower end of left tibia. Sensitivity to Amikacin and Imipenem was found on pus culture. So patient was started with these antibiotics. However, pain was not relieved. So arthrodesis was done, and curetted material was sent to histopathology lab where it was diagnosed xanthogranulomatous osteomyelitis. The patient was followed-up for 1 month. He did not have any complaints. All the previously existing complaints subsided. Xanthogranulomatous inflammation can be seen in bones also, though rarely reported.